Pengaruh Literasi Keuangan Terhadap Minat Masyarakat Dalam Menggunakan Pinjaman Online Pada Masyarakat Kota Kupang - Zelyn Jayanti Margaretha Ratuarat; Novi Theresia Kiak; Maria Indriyani Hewe Tiwu (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Online loans are currently increasingly popular among the public with the development of technology. The sophistication of this technology has had a very significant impact on the survival of society, which will make people more consumptive through the arrival of electronic or non-cash means of payment, without cash this will create impulsive shopping behavior where someone buys products without planning. This research aims to analyze the influence of financial knowledge on online loan interest behavior, to determine the influence of financial behavior on online loan interest and to determine financial attitudes towards online loan interest in the Kupang city community. This research uses primary data by distributing questionnaires online to 100 respondents in Kupang City who are online loan users. This research uses non-probability purposive sampling. Data analysis in this research uses multiple linear regression analysis with the results of the research showing that financial knowledge, financial behavior and financial attitudes have a significant effect on interest in online loans among people in Kupang City.